Measurement-based performance analysis of cooperative diversity for satellite terminals in a Moving Convoy - König, Jonas; Ihlow, Alexander; Arndt, Daniel; Heuberger, Albert; Del Galdo, Giovanni (IEEE Vehicular Technology Conference, 2013)
In this paper we discuss the impact of cooperative satellite diversity on the availability of the land mobile satellite (LMS) channel. By the use of multiple terminals the overall probability to encounter conditions where all terminals are in a bad channel state is reduced. This reduction depends on the number of terminals and the terminal distance. The results presented in this paper are completely based on the analysis of measurements. These were conducted for two geostationary satellites and four different environments using a single mobile satellite terminal. Thus, in order to virtually increase the number of terminals we rely on a convoy scenario using shifted versions of the data. Analyzing up to four cooperative terminals and different terminal distances a significant bad state reduction is already achieved for rather small distances. © 2013 IEEE.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Cooperative diversity; Cooperative satellite communications; Land mobile satellite channel; Propagation